Performative Aspekte des Rakugo-Theaters - Till Weingärtner (Bunron)
What is most important about a Rakugo performance? Is the performer supposed to follow a set of norms? Or is he free to do as he likes in order to entertain the audience? Using Fischer-Lichte’s concept of performance, this paper examines current trends in Rakugo theory and criticism, discussing the approaches of Horii Ken’ichi and Hirose Kazuo, as well as examples of contemporary Rakugo artists such as Shunpūtei Shōta or Kawayanagi Tsukushi, in whose performances the performative aspect of Rakugo comes to the fore.